On Monotony and Comonotony Approximation by algebraic polynomial - Zuhair Abd AL-Sada, Nada (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we are proved that if the function , change the monotone finitely many times in an interval , then there exist an algebraic polynomial , which comonotony of approximation with at every point in an interval , such that the best approximation can be estimate by